Exploring adoption and implementation of strategic management tools and techniques by listed companies in the Sri Lankan contex - Indrani, M.W.; Naidoo, M.; Wickremasinghe, G. (Faculty of Management Studies & Commerce, University of Jaffna, 2020)
The strategic management tools and techniques, also known as modern management accounting (MA) techniques, support managers in all stages of the strategic management process of businesses to achieve better performance. However, literature review evidenced that compared to traditional MA techniques the use of modern MA techniques is low particularly in developing countries. This study thus, explores the extent to which listed companies in Sri Lanka apply selected strategic management tools and techniques: target costing, kaizen costing, balanced scorecard and benchmarking stressing influences and variations among industry sectors with these practices. This study applies the Mixed Method Research approach with its QUAN + qual paradigm. Using a multi-stage purposeful random sampling technique, 42 listed companies were selected demonstrating five industry sectors. Interviews and discussions were conducted preferably with Finance executives of companies to verify the responses to the survey which is the main source of data. Findings advocate that contrary to the low application of modern MA techniques shown in the literature, Sri Lankan companies demonstrate a high level of application of four techniques observed. Even if target costing is not applicable for the whole plantation sector, they demonstrate rather high application of other techniques observed as they often deal with international markets where excellent quality is very important. Findings ratify that extent of application of techniques varies among sectors, mostly induced by factors such as: the nature of products, processes, and markets; stage of the business; size of companies; and the impact of environmental changes on businesses. It concludes that overall Sri Lankan companies are in a view that these practices certainly facilitate them, in keeping aligned product prices with market prices and accompanying quality of products that are essential in surviving in such highly competitive markets while retaining a satisfactory margin securing brand reputation.
Keywords: Strategic management tools and techniques; Industry sectors; Listed companies; Product improvement; Cost reduction